Give me some info one what Jenny and Jeremy did and I can help you solve this :)
Using the distributive property, an equivalent expression would be 6-16y
Comment the correct answer.
H(h(x)) means to use the entire function h(x) as the x value in the function h(x)..
h(h(x)) = (x²+1)² + 1
= (x²+1)(x²+1) + 1
= (x^4 + x² + x² + 1) + 1
= x^4 + 2x² + 2
g(h(x)) means to use the entire function h(x) as the x value in the function g(x)..
g(h(x)) = 3(x² + 1)
= 3x² + 3
g(h(x))
Answer:625
625 in delta math
Step-by-step explanation: